Financial Literacy of College Students of Siddharthanagar Municipality (The Lumbini Journal of Business and Economics, 2022)
This study analyzed financial literacy level of students’ pursuing bachelor and master’s degree from the college of Siddharthanagar municipality. Demographic characteristics (gender, age, parents’ income, parents’ occupation and ethnicity) and educational characteristics (level, stream and division) are taken as independent variables to know their effect on financial literacy level. Total population was 6794 from seven colleges located in Siddharthanagar municipality. Out of the population, 378 sample size were withdrawn by using Yamane formula and questionnaires were distributed among them by quota sampling technique. Collected data were described by frequency, percentage, mean and standard deviation, and two hypotheses were tested using independent sample T-test, and remaining six hypotheses were tested by using one-way ANOVA. Within ANOVA test, further comparison in between groups is done using Post-Hoc Test. By analyzing the result of statistical result it is concluded that the demographic characteristic like age, gender and ethnicity were significant to financial literacy whereas parents’ income and parents’ occupation did not have impact on financial literacy level of students. In other hand, the educational characteristic variable like level, stream and division were significant to financial literacy of students.